The Nuance of Affirmation: The Epistemological Foundation of Sundanese Wisdom - Djunatan, Stephanus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2009)
One who learns and reads Western Philosophy is familiar with theDecartes' proposition 'cogito ergo sum'. This proposition becomesontological and epistemological reason of our existence.Nevertheless, one can also explore another reason of existence, notonly this Cartesian proposition considered the universal. A nuanceof affirmation implied within a local tradition of wisdom can be theother ontological and epistemological reason. Therefore, anexploration the nuance of affirmation in Asian tradition of wisdomis necessarily discovered this alternative reason of existence (1).One can discover such alternative reason from a local worldviewand philosophical narration in a local tradition of wisdom (2). Thisarticle observes the worldview and philosophical narration ofSundanese people. The observation offers a further interpretationto the Sundanese worldview and philosophical narration. Thepurpose of this interpretation is to formulate the nuance ofaffirmation as it is implied in the local system of knowledge. Aprinciple of affirmation is derived from the interpretation of thesystem of knowledge (3). The interpretation also becomes a furtherinvitation to explore and to find out an intercultural understandingand dialogues of various systems of knowledge (4).